Implementation of Sumbawa’s Regent Decree No 801 on The Formation of 2016 Moyo Festival Executive Committee in Order to Encourage Economic Creativity and Society Innovation (Study at Youth, Sports and Tourism Agency of Sumbawa Regency) - Muhammad Ariy Dermawan Sanapiah; Agus Suryono; Luqman Hakim (Sekolah Pascasarjana Universitas Brawijaya, 2018)
Implementation of Sumbawa’s Regent Decree No 801 on the Formation of 2016 Moyo Festival Executive Committee in order to Encourage Economic Creativity and Society Innovation. A great amount of either natural riches or Indonesian culture is a very promising tourism potential. One of the regions owning a good potential is Sumbawa Regency. Tourism potential owned by this regency then draws the government’s attention to able to manage and develop it. The national regulation related to tourism is regulated in Law No 10/2009 on Tourism. Sumbawa Regency alone issued a policy to develop the tourism called Sumbawa’s Regent Decree No 801 on the Formation of 2016 Moyo Festival Executive Committee. Moyo Festival had a purpose to be able to increase the tourist visit and the promoted Sumbawa Regency so that it could encourage economic creativity and society innovation. The research results showed that the implementation of Moyo Festival was not optimal yet to increase the tourist visit and the promoted Sumbawa. Besides, the encouragement to the economic creativity was not optimal either.